Dephosphorylation in nuclear reassembly after mitosis - Archambault, Vincent; Li, Jingjing; Emond-Fraser, Virginie; Larouche, Myreille (Frontiers in Cell and Developmental Biology, 2022)
In most animal cell types, the interphase nucleus is largely disassembled during mitotic entry. The nuclear envelope breaks down and chromosomes are compacted into separated masses. Chromatin organization is also mostly lost and kinetochores assemble on centromeres. Mitotic protein kinases play several roles in inducing these transformations by phosphorylating multiple effector proteins. In many of these events, the mechanistic consequences of phosphorylation have been characterized. In comparison, how the nucleus reassembles at the end of mitosis is less well understood in mechanistic terms. In recent years, much progress has been made in deciphering how dephosphorylation of several effector proteins promotes nuclear envelope reassembly, chromosome decondensation, kinetochore disassembly and interphase chromatin organization. The precise roles of protein phosphatases in this process, in particular of the PP1 and PP2A groups, are emerging. Moreover, how these enzymes are temporally and spatially regulated to ensure that nuclear reassembly progresses in a coordinated manner has been partly uncovered. This review provides a global view of nuclear reassembly with a focus on the roles of dephosphorylation events. It also identifies important open questions and proposes hypotheses.